Familial Predisposition of Primary Dysmenorrhea among Senior High School Girl Students - Prema Sharlini; Hadyana Sukandar; Ryadi Fadil (Althea Medical Journal, 2015)
Background: Dysmenorrhea is a common female reproductive problem in women of active reproductive age which is characterized by menstrual pain or cramps in a women’s lower abdomen or back. Dysmenorrhea can be classified into primary and secondary. One of the associated risk factor of primary dysmenorrhoeais the family history, however the study on the family history of primary dysmenorrhea with recurrent menstrual pain is limited. This study was conducted to identify the correlation between family history and primary dysmenorrhea in high school girls.